Reforma del art. 392 numeral 13 del código orgánico Integral penal, en relación a la sanción exclusiva Con multa para las empresas o personas naturales Que no han registrado el traspaso de dominio de Varios vehículos - Pullutasig Condemaita, Ángel Polivio (2016)
The Code of Criminal Integral says in Art. 51 that the penalty is a fee to freedom and the rights of individuals, as a legal consequence of their actions or omissions punishable. In the case of traffic violations it is set to penalties, restriction of liberty, fines equivalent worker unified general basic wages and reducing points to the driver's license. In Art. 392, in paragraph 13 of the Code Integral Criminal such as violation of traffic seventh class, shall be punished the person with a fine equivalent to five percent to a unified basic wage of workers in general and reduction of one point five points in the driver's license, or for the buyer of a motor vehicle not registered under transit agency concerned, the transfer of ownership of the property, within thirty days from the date of the respective contract. This measure of registering the transfer of the property, serves as a means for controlling the purchase and sale of motor vehicles, and thus the taxes that are paid by law. But it is the case that a company or a person who buys several vehicles, and through no fault of their obligation to register their vehicles do not realize in due time situations, you must in this case pay only the fine and not the rebate points to the driver's license, because the act an accumulation of points would become the driving license of the owner of several acquired vehicles, and more if it is a legal person, may not apply point reduction because it is a fictitious person, which would rest him the legal representative of the company, which also lead to the accumulation of points, so I think in this case, they are punished only with a fine, and so to be based on Art. 71 of the Code Integral Criminal Procedure, are specific penalties applicable to legal persons, including the fines. The legislature should provide for the reduction points to the driver's license for the transfer of a vehicle, applies only to natural persons and if it is several vehicles must be taken into account only the fine, because it is required by law and enjoyment procedure of legal certainty, as guaranteed by Art. 82 of the Constitution of the Republic of Ecuador, that rules should be clear, precise and applicable to the relevant authorities.